1994
DOI: 10.1139/t94-009
|View full text |Cite
|
Sign up to set email alerts
|

Displacement pile behaviour in glacial clay

Abstract: The paper describes a programme of field experiments with heavily instrumented displacement piles installed in a stiff, lodgement till. Measurements of the effective stresses recorded at various levels along the pile shaft during installation, equalization, and load testing are presented. Shaft capacity is shown to be governed by an effective stress failure criterion, with the mobilized stresses depending on the clay consistency, distance from the pile tip, shaft surface texture, type of loading, installation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 0 publications
1
22
0
2
Order By: Relevance
“…This can be seen in the work of Marsland & Powell (1980), who, carrying out a series of large-diameter cyclic plate load tests in the same till deposit, showed that there was no significant change in ultimate capacity measured by CRP testing after cyclic loading, but there was an overall stiffening of response in the pre-yield phase. Lehane & Jardine (1994), testing model jacked-in displacement piles at the same site, concluded that retesting the piles resulted in alteration of the soil fabric, described as plastic hardening, with radial effective stresses being approximately 15% higher in all retests. However, the relative disturbance of the soil fabric is likely to be greater for a displacement pile than for the auger-bored pile described here.…”
Section: Analysis Of Rapid Load Tests In Glacial Tillmentioning
confidence: 99%
“…This can be seen in the work of Marsland & Powell (1980), who, carrying out a series of large-diameter cyclic plate load tests in the same till deposit, showed that there was no significant change in ultimate capacity measured by CRP testing after cyclic loading, but there was an overall stiffening of response in the pre-yield phase. Lehane & Jardine (1994), testing model jacked-in displacement piles at the same site, concluded that retesting the piles resulted in alteration of the soil fabric, described as plastic hardening, with radial effective stresses being approximately 15% higher in all retests. However, the relative disturbance of the soil fabric is likely to be greater for a displacement pile than for the auger-bored pile described here.…”
Section: Analysis Of Rapid Load Tests In Glacial Tillmentioning
confidence: 99%
“…It is apparent that additional testing of large diameter, high capacity piles ,where radial effective stresses are measured throughout installation, equalisation and load-testing, is required in order to address many of the uncertainties that remain in current pile design methods. Undrained Strength, s u (kPa) Adhesion Factor, α Tomlinson(1957) Peck (1958) Woodward (1961) Kerisel ( Tomlinson(1957)   λ approach, Vijayvergiya and Focht (1972)   API 1(1976API 1( -1986   API 2(1976API 2( -1986   Semple and Rigden (1984)   Randolph and Murphy (1985)   API(1987-Present)   Kolk & van der Velde (1996)   NGI-99, Karlsrud et al (2005)   Lehane and Jardine (1994a) Bothkennar Low OCR shallow marine clay Lehane and Jardine (1994b) Pentre Low OCR Glacio-Lacustrine silty clay Chow (1997) …”
Section: Discussionmentioning
confidence: 99%
“…Both onshore test sites have extensive histories of pile testing activities (e.g. Lehane and Jardine, 1994;Chow, 1997;Jardine et al, 2006), and consequently the sites have been reasonably characterised through field testing and laboratory experiments (e.g. Powell and Butcher, 2003).…”
Section: Sites and Characterisationmentioning
confidence: 99%